Konsortium Transnasional Berhad / Muhammad Aiman Shaari, Hazami Zulkifli and Mohamad Nor Efiezal Mukminin Mohd Fadzil - Shaari, Muhammad Aiman; Zulkifli, Hazami; Mohd Fadzil, Mohamad Nor Efiezal Mukminin (2018)
Konsortium Transnasional Berhad (KTB) is a company that provide a service involving buses, including express bus service, a bus service that run much faster than usual bus. Express bus only two stop in each trip, where they pick the passengers on the bus the bus terminal and drop on other bus terminal, usually much further or out of the city. Passengers supposed to book their ticket early from the counter where they have to walk into the ticket counter or they can book on the internet. The ticket price usually depends on how far the destination.The bus trip will take from 1 and up to 7 hour on the road, then they drop the passengers on the terminal where the passengers want, depend on the ticket.